Infantile gastroesophageal reflux in a hospital setting - Leonard Michael S; Roach Christine M; Baker Susan S; Baker Robert D (BMC, 2008)
Abstract Background Gastroesophageal reflux is a common diagnosis in infants. Yet, there is no information on the demographics of those hospitalized with reflux. The aim of this study is to describe the demographics of children with gastroesophageal reflux discharged from the hospital during the first two years of life. Methods Retrospective chart review of children aged 0-2 years discharged between January 1, 1995 and December 31, 1999 with a diagnosis of reflux documented in their hospital chart prior to 12 months of age. Results Reflux was the seventh most common reason for hospitalization. About 50% of subjects with reflux had multiple hospitalizations. Of the 1,096 infants diagnosed with reflux about half were born prematurely. Reflux was the primary diagnosis for 21% of all infants; 10% of those born prematurely. The average length of stay for the subjects was longer than the hospital average. African Americans, 2.4% of the population, accounted for 29% of discharges. Caucasians, 86% of the population, were 66% of discharges. 21.8% of African Americans and 68.3% of Caucasians were diagnosed with reflux. 35% of mothers smoked, 27% worked and 48% had public insurance, compared to 22.2%, 57%, and 24% respectively of females in the general population. Conclusion Reflux is a common discharge diagnosis. Children who have primary reflux have longer than average hospital stays. About half had multiple admissions. Mothers of children with reflux are more likely to be less educated, receive public insurance, smoke, and be unemployed than the general female population in Western New York. Although African American children were disproportionately hospitalized, they were less likely to be diagnosed with reflux.